Los problemas vinculados con el genero y la participacion de las mujeres en la agricultura de riego: el caso de dos canales privados de riego en Carchi, Ecuador. In SpanishGender issues and women's participation in irrigated agriculture: the case of two private irrigation canals in Carchi, Ecuador - Bastidas, E.P. (International Water Management Institute, 2000)
Defines the degree of women's involvement in irrigated agriculture and water users associations in two private irrigation canals in Ecuador and identifies factors that limit their involvement. Analyzes the effects of intra-household dynamics and the women's urban/rural backgrounds on participation.